Sticky : the secret science of surfaces - Winkless, Laurie (Bloomsbury Sigma, 2022)
"In Sticky, Laurie Winkless explores some of the ways that friction shapes both the manufactured and natural worlds, and describes how our understanding of surface science has given us an ability to manipulate stickiness, down to the level of a single atom"--